2018
DOI: 10.1111/iej.13036
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of apoptosis/necrosis and cytokine release provoked by three root canal sealers in human polymorphonuclears and monocytes

Abstract: Aim To evaluate the in vitro cytotoxicity and cytokine release of three fresh root canal sealers and to determine the type of cell death they induce. Methodology The sealers tested were Sealer 26 (S26), AH Plus (AHP), and Endosequence BC Sealer (END). Fresh sealers were cultivated in contact with monocytes and polymorphonuclears (PMNs) obtained from the peripheral blood of humans. Cell viability, apoptosis and necrosis were analysed at 4 h (PMNs) or 24 h (monocytes) using Annexin‐V and propidium iodide in a cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…In the present study, EndoSequence BC Sealer, BioRoot RCS, and Endoseal MTA showed superior cell viability and migration ability compared to AH Plus. EndoSequence BC Sealer is a novel bioceramic tricalcium silicate-based sealer that has shown nontoxic and biocompatible results in previous studies [10,13,17,25,26]. It is a premixed sealer that will not change in terms of its properties during the mixing procedure [17].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, EndoSequence BC Sealer, BioRoot RCS, and Endoseal MTA showed superior cell viability and migration ability compared to AH Plus. EndoSequence BC Sealer is a novel bioceramic tricalcium silicate-based sealer that has shown nontoxic and biocompatible results in previous studies [10,13,17,25,26]. It is a premixed sealer that will not change in terms of its properties during the mixing procedure [17].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of cultures to AH Plus extracts reduced cell migration even at low concentrations. In epoxy resin sealers, the presence of cytotoxic by-products from polymerization reactions of the epoxy resin may have adversely affected cell migration [31].…”
Section: Discussionmentioning
confidence: 99%
“…Sufficient radiopacity enables clinicians to distinguish between adjacent anatomical structures and sealers and evaluate the quality of the root canal fillings 31 . All sealers tested presented radiographic densities higher than recommended value, with AHP being the highest one, also observed in other studies 26,32 . Nevertheless, excessive radiopacity of a sealer could hide obturation failures.…”
Section: Discussionmentioning
confidence: 87%
“…31 All sealers tested presented radiographic densities higher than recommended value, with AHP being the highest one, also observed in other studies. 26,32 Nevertheless, excessive radiopacity of a sealer could hide obturation failures. BC and MF present, respectively, zirconium oxide and calcium tungstate radiopacifiers, while AHP and SP exhibit both of them.…”
Section: Discussionmentioning
confidence: 99%